Applying Picture Series to Promote Students’ Writing Achievement on Recount Text - Aminatun, Dyah; Putri, Nikenda (IJLHE: International Journal of Language, Humanities, and Education, 2023)
This research was conducted to find out the improvement of students’ writing skill on recount text by using picture series and to know the process of implementation of picture series in teaching writing on recount text to the tenth-grade students of SMA Gajah Mada Bandar Lampung. The subjects of this research were 30 students of X IPA 1 at SMA Gajah Mada Bandar Lampung. This research was used classroom action research. Furthermore, the data collected through qualitative and quantitative data. The researcher used interviews, and observation checklist in collected the qualitative data and used tests in collected the quantitative data. The research findings reveal that the using picture series to improve students’ writing skills, particularly recount text, was beneficial. Students’ writing scores also demonstrated an improvement in their writing abilities. The increasing mean score from pre-test until post-test 2 is 12.96. The students’ attitudes towards studying English are also improving, as indicated by their increased participation in class. It can be concluded that, by using picture series media, the students’ writing skill is improved.